Salivary hormones and anxiety in winners and losers of an international judo competition - Papacosta, E.; Nassis, G. P.; Gleeson, M. (Journal of Sports Sciences, 2016)
The purpose of this study was to investigate the responses of salivary hormones and salivary secretory immunoglobulin A (SIgA) and anxiety in winners and losers during an international judo competition. Twenty-three trained, male, national-level judo athletes provided three saliva samples during a competition day: morning, in anticipation of competition after an overnight fast, mid-competition, and post-competition within 15 min post-fight for determination of salivary cortisol, salivary testosterone, salivary testosterone/cortisol ratio, SIgA absolute concentrations, SIgA secretion rate and saliva flow rate. The competitive state anxiety inventory questionnaire was completed by the athletes (n = 12) after the first saliva collection for determination of somatic anxiety, cognitive anxiety and self-confidence. Winners were considered 1-3 ranking place (n = 12) and losers (n = 11) below third place in each weight category. Winners presented higher anticipatory salivary cortisol concentrations (p = 0.03) and a lower mid-competition salivary testosterone/cortisol ratio (p = 0.003) compared with losers with no differences for salivary testosterone. Winners tended to have higher SIgA secretion rates (p = 0.07) and higher saliva flow rates (p = 0.009) at mid-competition. Higher levels of cognitive anxiety (p = 0.02) were observed in the winners, without differences according to the outcome in somatic anxiety and self-confidence. The results suggest that winners experienced higher levels of physiological arousal and better psychological preparedness in the morning, and as the competition progressed, the winners were able to control their stress response better.